Amyloid Goiter: A Diagnosis to Consider in Diffuse Fatty Infiltration of the Thyroid. (4th March 2017) - Bakan, Selim; Kandemirli, Sedat Giray; Akbas, Serkan; Cingoz, Mehmet; Ozcan Guzelbey, Burcu; Kantarci, Fatih; Akman, Canan
Abstract : An amyloid goiter is the presence of amyloid protein in the thyroid in sufficient amounts to produce enlargement of the gland, accompanied by fat deposition of varying extents. It can be seen in long‐standing inflammatory disorders such as familial Mediterranean fever. Imaging findings depend on the amount of fat and amyloid deposition; however, the main imaging finding is diffuse fatty infiltration of the thyroid. Herein, the multimodality imaging features in 3 cases of amyloid goiters secondary to familial Mediterranean fever are presented.